Prediction of hard cardiovascular events in HIV patients. (2nd September 2016) - Raggi, Paolo; De Francesco, Davide; Manicardi, Marcella; Zona, Stefano; Bellasi, Antonio; Stentarelli, Chiara; Carli, Federica; Beghetto, Barbara; Mussini, Cristina; Malagoli, Andrea; Guaraldi, Giovanni
Abstract : Objectives: To assess the accuracy of risk prediction algorithms used in the general population and an HIV-specific algorithm to predict hard cardiovascular events. Methods: We compared the pooled equation algorithm (PE) proposed by the American Heart Association with the Framingham risk score (FRS) and the HIV-specific DAD (Data Collection on Adverse Effects of Anti-HIV Drugs) algorithm in a cohort of 2550 HIV+ patients followed for 17 337 patient-years. Results: During follow-up we recorded 67 myocardial infarctions and 2 cardiovascular deaths. PE and FRS identified and missed the same number of events (44 of 69 identified by PE and 49 of 69 by FRS). Similarly, DAD and FRS predicted and missed the same number of events (38 of 64 and 44 of 64 identified, respectively). All algorithms showed moderate sensitivity, specificity and positive predictive values, but high negative predictive values. However, PE and DAD identified more patients with no events than FRS (13.8% and 9.3% net reclassification improvement, respectively). Conclusions: All algorithms showed a modest predictive ability, although the PE and DAD algorithms identified more patients at low risk.